Use of Econometric Models in Marketing Research - Azimovna, Musayeva Shoira; Ulugbekovna, Ruzikhulova Nilufar; Sherzod, Qunishev (International Journal on Orange Technologies, 2023)
The article examines the problems of growing, processing, and selling fruits and vegetables and highlights the issues of conducting marketing research and using econometric methods to solve them.